Transcription of the transforming region of adenovirus type 5 in a rat cell line transformed by a small restriction fragment. - Chinnadural, G (1978)
The fraction of the adenovirus type 5 genome expressed as mRNA in a rat cell line, 5RK, transformed by the HsuI-G restriction fragment was analyzed by saturation hybridization using separated strands of 32P-labeled HindIII-G fragment. It was found that 45 to 50% of G fragment (about 8 X 10(5) daltons) is expressed as mRNA. The size of polyadenylic acid-terminated virus-specific cytoplasmic and nuclear RNA was determined by electrophoresis on polyacrylamide gels containing 98% formamide, followed by hybridization of gel slices with viral DNA. The major virus-specific RNA species present in the cytoplasm is about 14S, whereas the major virus-specific RNA present in the nucleus is 30 to 32S. The large size of nuclear virus-specific RNA suggests that host sequences are covalently linked to the viral transcript.